PPVT-I administration rules significantly shorten PPVT-III/IV administration. (4th May 2017) - Besha, Xi Sheng; Spencer, Robert J.; Bieliauskas, Linas A.
Abstract : This study evaluated whether using the Peabody Picture Vocabulary Test-First Edition (PPVT-I) basal and ceiling criteria would result in similar estimates of receptive vocabulary while permitting administration of fewer test items when using the third and fourth editions of the PPVT. Data were retrospectively collected from 119 adult inpatients who completed a neuropsychological screen that included the PPVT-III or PPVT-IV, which were re-scored using PPVT-I criteria. PPVT-III/IV raw scores were not significantly different from PPVT-I raw scores. Although the difference between the PPVT-III/IV and PPVT-I standard scores was statistically significant, the difference was less than 8 points in 95% of cases. On average, 15 fewer items would be administered using the PPVT-I rules, leading to shorter administration time.